Panoptik Lingkungan Sekolah Berasrama di SMAN Cahaya Madani Banten Boarding School - Maulana, Ari Fathin; Setiawan, Rizki (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
This research examines applying the panoptic concept in the supervision system at SMAN Cahaya Madani Banten Boarding School which aims to understand the influence of supervision on student behavior, perceptions of freedom, and the role of teachers and staff in a boarding education environment. This research expands the understanding of how the application of the panoptic concept when in a boarding school environment that has different rules from other boarding schools. A qualitative approach with a constructivist paradigm explored individual experiences through observation, interviews, and documentation. The results showed that the supervision system at Cahaya Madani Banten Boarding School, through the use of CCTV technology, strict rules, and direct supervision by teachers and student council, is effective in shaping student discipline. However, intensive supervision also poses challenges, such as psychological pressure and limited student freedom. Some students find this supervision helpful in developing manners and self-control, while others feel stressed by the hectic routine. This study provides insights into the importance of balancing supervision and freedom to create an educational environment that supports students' character development.